Does generation X and Y differ in the Islamic work ethics: a study among employees in Islamic banks - Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Fauzi, Fatin; Melati, Putifatma Hanum (Global Business and Social Entrepreneurship Resources, 2017)
A generational difference is a product of social construct. Each generation has its own distinctive features of characteristics, attitudes and values. Understanding and knowing the differences are important to handle differences between generations. This study aimed to investigate whether generations X and Y differ in Islamic Work Ethics. It is hypothesized that there is a significant difference between generation X and Y in Islamic Work Ethics. 225 full-time bank employees around Kuala Lumpur were participated in the study. The sample comprised different levels of job positions that represented different generational cohorts. Two measures were used in the study. First, the work ethics was measured by the Islamic Work Ethics Scale (Ali, 1988). Second, generational cohort was measured through a single item question that was their year born. Result suggested that there is no significant difference in scores for generations X and Y in work ethic. The finding supports the existing literature that values and ethics are usually transmitted from one generation to another without being affected by historical events happened in a particular cohort. Implications and suggestions are discussed concerning the possibility of implementation, teaching and promoting Islamic Work Ethics among different generations in the banking institutions.